Price Discount and Impulse Buying at Diamond Game Mobile Legend Bang Bang - Darma Gumelar; Fitri Lestari (Jurnal Ilmu Manajemen dan Ekonomika, 2023)
Mobile Legends Bang Bang (MLBB) is one of the most popular mobile games in Indonesia. Since its launch in 2016. It can be played by more than one person in an area, usually 5 vs 5 and the main goal of the Mobile Legends Bang Bang game is to destroy the opponent's base. This game also utilizes in-app purchases for its monetization, and diamond is the term for money in the mobile legends Bang Bang game to make purchases in the Mobile legends Bang Bang game. Therefore, researchers are interested in conducting research on purchasing diamonds on the Mobile Legends Bang Bang site. This study aims to determine how much influence the price discount has on impulse buying in Mobile Legends Bang Bang diamonds. The research method used by the authors is descriptive and verification research, while the sample in this research is consumers of the Mobile Legends Bang Bang game. The research was conducted January – Mei 2023 with a sample of 100 respondent who were Mobile Legends Bang Bang. The data analysis technique used is a Hypothesis Test design with Validity Test, Reliability Test, Normality Test, Simple Linear Regression Analysis, Correlation Coefficient, Determination Coefficient, and t test. The results of the study show that the price discount has a significant effect on impulse buying.